Counselling Skills and Competencies Tool: Scale Development and Preliminary Data - Jane L. Fowler; John G. O'Gorman; Mark P. Lynch (Psychotherapy and Counselling Journal of Australia)
This paper reports on the development of the Counselling Skills and Competencies Tool (CSCT) as a practical instrument that can be used in teaching and assessing counselling skills and competencies. Members of an entry-level counselling course, experienced and beginning counsellors, and people not involved in the counselling profession, assisted in the development and validation process. The outcome was a 23-item, six-scale tool measuring Attending, Reflecting, Questioning, Therapeutic Alliance, Core Counselling Conditions, and Facilitating the Session. The CSCT includes the range of skills and competencies expected of beginning counsellors, was constructed in a way that assists feedback to trainees, and received good interrater and test-retest reliability with this sample. Used appropriately, it has the potential to improve counsellors’ assessment skills in training, and in turn the effectiveness of their subsequent practice.